Moeda, mercadoria e crise mercantil: os debates econômicos na Inglaterra durante a década de 1620 - Carlos Eduardo Suprinyak (2010)
The study proposes to investigate the economic ideas which came to light in early 17th century England from the standpoint of a specific historical episode: the great commercial crisis which took hold of the kingdom between approximately 1619 and 1623. The urge for understanding the phenomena behind the crisis gave rise to a great amount of public debates which culminated in the creation of some of the periods most representative economic literature in particular the works of Gerard de Malynes, Edward Misselden and Thomas Mun. The interpretation of such works as part of a historiography of mercantilism ends up obscuring important parts of their true historical meaning, which is lost amidst the systematization effort. The perspective here assumed seeks to place ideas in their proper context, taking into consideration the impact of short- and long-term underlying conditions but without falling back into mere historical determinism; the evolution of ideas is seen as the result of discursive interactions which occur in the public sphere circumscribed by a discursive context, but still retaining a space for self-determination. Initially, the study recovers the material and institutional conditions which characterized early modern England, describing next the socio-political and economic scenario prevalent during James Is reign (1603-25). After that, the analysis shifts to the economic reasoning of the period and the evolution of the public debates surrounding the crisis, seeking to understand in detail the processes of change and of dissemination of ideas, and concluding that the peculiar traits of the economic literature which was then produced are directly related to the dynamics which the debates assumed. Finally, the episode is briefly located within an ampler historical perspective.